Evaluation Of Settlements On The Coastal Regions Of Thrace Regarding Current Laws And Regulations - Eren, Z. O.; Çevik, Gülay; Korkmaz, Z.; Gökdemir, M.; TÖRE, EVRİM ÖZKAN (Scibulcom Ltd, Po Box 249, 1113 Sofia, Bulgaria, 2012)
During the last 3 decades, the coastal areas of Thrace sub-region have become a favourite summer resort for the inhabitants of Istanbul who are in need of running away from the metropolis jam and in aspiration of holiday and nature. From 1980's till today, the tourism activities on the coastal regions have had a great influence on land use, while the sea front and the natural areas have confronted with a great pressure of second home development. This process is encouraged by the zoning legislation which is environmentally insufficient and the law regarding environment which has lately come into force. Therefore, the infringement of areas subject to public interest and the destruction of natural resources is ineviatable to be hindered which in consequence triggers lots of problems. In this study, the second home development on the coastal areas of the sub-region is analysed regarding the effects Of related codes and regulations. The analysis mainly reveals the lack of an effective legislative infrastructure and a management model regarding the coastal areas.
Keywords: Second Homes (summer houses); Coastal Areas; Zoning Legislation; Trakya Alt Bölgesi; İkinci Evler (yazlık evler); Kıyı Bölgeleri; İmar Mevzuatı; Thrace Sub-Region